An ‘ethic of care’ in clinical settings: encompassing ‘feminine’ and ‘feminist’ perspectives - Bowden, Peta (Nursing philosophy, 2000)
Recent work in clinical nursing ethics has been influenced by two main areas of insight associated with the challenge levelled by the women's movement to traditional thinking about morality and ethics. Broadly speaking these two realms have been distinguished as articulating ‘feminist’ socio-political and ‘feminine’ ethic of care concerns. Often these two impulses are seen as pulling against each other, or worse, the ‘feminine’ emphasis on the ethics of care is seen as reinforcing the dynamics that elicit the ‘feminist’ concern. In this paper I suggest how an expanded understanding of an ethic of care in clinical settings can provide resources for dealing with both concerns. A discussion of the way institutional relations can ride rough-shod over the ‘feminist’ insights of ethical care, in the second part of the paper, provides evidence for my conclusion that ethical nursing care depends on recognizing that both areas of insight are imperative for its success.